Evaluation of the efficacy of a new inactivated vaccineagainst Staphylococcus aureus, Echerchia coli andMycoplasma bovis mastitis in cows - Zengin, Hilal; Alkac, Zeliha Keskin; Vezir, Yaser; Tanyildizi, Sadettin; Korkak, Fatih Ahmet; Hark, Betul Dagoglu; Dagoglu, Gurdal (Ist Zooprofilattico Sperimentale Abruzzo & Molise G Caporale-Izs A&M, 2024)
Staphylococcus aureus, Escherichia coli and Mycoplasma bovis are the most commonly isolated mastitis pathogens. The aim of this study was to evaluate the efficacy of a new mixed vaccine against mastitis caused by Staphylococcusaureus, Escherichia coli, and Mycoplasma bovis. For this purpose, a mixed inactivated vaccine was administered subcutaneously to 24 heifers as one dose (2 mL) on the 45th day before birth and the second dose 21 days later. In 9heifers, 2 mL of PBS was administered as placebo instead of vaccine. Then, heifers were divided into 3 groups as 7vaccinated and 3 unvaccinated animals. Staphylococcus aureus, Escherichia coli, and Mycoplasma bovis were administered to the groups through intramammary route. Three vaccinated heifers were considered the commoncontrol without bacteria in all groups. The parameters considered to assess the effect of vaccination were clinical findings, bacterial count in milk, somatic cell count, and antibody titers. Clinical signs were observed only in the unvaccinated placebo group. Bacteria count and somatic cell count in milk increased in vaccinated and unvaccinated heifers. However, this increase was less in vaccinated animals and gradually returned to the normal level. In the unvaccinated heifers, it was ever high. Serum antibody titers were measured before and after vaccination. Antibody titers were high in vaccinated heifers after vaccination and were negative in unvaccinated heifers. In conclusion, the mixed vaccine had beneficial effect against Staphylococcus aureus, Escherichia coli, and Mycoplasma bovis mastitis and stimulated the immune response of vaccinated heifers.
Keywords: Cows,; inactive vaccine; mastitis